Enseñanza de la ética en las escuelas de medicina peruanas: un estudio de sílabos - Cárdenas Díaz, Maximiliano (2013)
Objectives: To describe the general characteristics of medical ethics education, teaching methods and assessment, objectives, areas content and readings required as contained in Peruvian medical schools syllabi. Design: Descriptive, transversal, observational study. Setting: Institute of Ethics in Health, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Material: Ethics course syllabi. Methods: Information of 25 ethics course syllabi corresponding to 22 medical schools were used: 13 public and 9 private (three schools had two courses). Data contained in the syllabi were analyzed using SPSS version 15 and Atlas ti for qualitative analysis. Main outcome measures: Characteristics of teaching on ethics. Results: All Peruvian medical schools required ethics course in their curricula. Most frequent name was Ethics and deontology. Most schools had only one course (n=19) and three had two. There was no course on ethics during internship. The course on ethics represented only 1% (2% in schools with two courses) of total credits required for graduation as a physician in our country. The most frequent method of teaching was in the classroom and not in clinical settings. All schools assessed ethics learning through knowledge tests. The most frequent objective was knowledge (43%) and the most frequent content area was professionalism (21%). The 25 syllabi listed 240 readings, being the most frequent the Colegio Medico del Peru’s Code of Ethics. Conclusions: There is necessity of consensus for ethics education in our medical schools.